2005
DOI: 10.1002/eji.200425767
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptides from human pathogens able to cross‐activate an HIV‐1‐gag‐specific CD4+ T cell clone

Abstract: Antigen recognition by T cells is degenerate both at the MHC and the TCR level. In this study, we analyzed the cross‐reactivity of a human HIV‐1 gag p24‐specific CD4+ T cell clone obtained from an HIV‐1‐seronegative donor using a positional scanning synthetic combinatorial peptide library (PS‐SCL)‐based biometrical analysis. A number of decapeptides able to activate the HIV‐1 gag‐specific clone were identified and shown to correspond to sequences found in other human pathogens. Two of these peptides activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…Our previous studies on T cell pathogen specificity have shown that more than one peptide can be recognized by a single pathogen specific T cell clone [47], [49], [52]. However, this was not the case in this work in which only one vaccinia epitope was found to stimulate each of the clones.…”
Section: Discussioncontrasting
confidence: 66%
“…Our previous studies on T cell pathogen specificity have shown that more than one peptide can be recognized by a single pathogen specific T cell clone [47], [49], [52]. However, this was not the case in this work in which only one vaccinia epitope was found to stimulate each of the clones.…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast to the genetic screen described here, which identifies single amino acid substitution APLs, PS-SCL screens peptides that are randomized at every position except one. While PS-SCL scanning has been shown capable of identifying superagonist analogs (25, 26), the need to deduce the sequence of the putative superagonists, and the subsequent testing of large numbers of potentially nonproductive altered peptide ligands which are non-cross-reactive for the native eptiope, present additional hurdles.…”
Section: Discussionmentioning
confidence: 99%
“…Without contact with allogeneic MHC molecules, the exposure to commensal bacteria or environmental antigens is also probably to induce potent heterologous immunity, which is one way for the generation of alloreactive memory T cells (23,24). Many studies have identified that alloreactive T-cell clones can also stem from other immune events (25,26), such as dozens of virus-specific (CMV, EBV, Flu, HIV, Zika Virus, SARS-CoV-2) memory T cells that show cross-reactivity to allogeneic pMHC complexes (27)(28)(29)(30)(31)(32). Thereby, these memory T cells can also pre-exist in the host even if they have not previously encountered donor-derived antigens.…”
Section: T Cells In Transplantationmentioning
confidence: 99%